Flood damage analysis for Kg. Datuk Dagang, Klang / Maureen Neging, Assoc. Prof. Dr. Wardah Tahir and Lydia Dundun Francis - Tahir, Wardah; Francis, Lydia Dundun (Research Management Institute (RMI), 2011)
Geographical Information System (GIS) application in flood management are largely utilised by the authorities around the world. GIS operations improve the efficiency of flood disaster monitoring and management in tropical countries like Malaysia. In this study, Geographic Information System (GIS) method is selected over other approaches namely; Penning-Rowsell & Chatterton and Narabeen Lagoon Floodplain Risk Management Plan. The study area, Kg. Datuk Dagang is located in area of South Klang. This area is near to the Klang River and has high potential of flooding. The focus of this study is to estimate flood damage at Kg. Datuk Dagang, Selangor on buildings and roads using Geographic Information System (GIS). This study has managed to quantify for flood damage costs for the lengths of inundation of 100 m through 300 m from the river. It is proven that the damage costs increase proportionally with the increase of the lengths of inundation.